Scattered-light Optical Isodynes-Basis for Threedimensional Isodyne Stress Analysis* - Pindera, J.T.
The paper presents the principles, theory, basic techniques, reliability and eficacy of the three-dimensional, non -destructive isodyne stress analysis. Analytical isodynes constitute the analytical component of the theoretical basis of two-dimensional and three-dimensional isodyne analysis of stresses in plates and some bulky bodies. The analytical isodynes can be obtained experimentally by means of optical isodynes which can be produced by scattered radiation under specified conditions. Theoretical bases of optical isodynes are discussed with regard to their theoretical admissibility, technical feasibility, and compatibility with the present state of knowledge. Included is discussion of the accepted mathematical models of the major physical phenomena, and discussion of the related reliability and efficacy of the isodynes. Within such a framework, isodyne stress analysis is compared with some related, typical procedures of stress analysis. Examples characterize the reliability and eficiency of the isodyne stress analysis in determination of components of actual three-dimensional stress states in plates, local effects including contact problems, fracture mechanics, and composite structures. Conclusions are based on the recognition that determination of the actual three-dimensional stresses in structures is of importance to